Clinical presentation of pediatric tuberculous spondylitis in high TB burden setting before and during the COVID-19 pandemic - Nazhira P Juslin; Djatnika Setiabudi; Heda M Nataprawira; Ahmad Ramdan (Journal of Infection in Developing Countries)
Introduction: Tuberculous spondylitis (TBS) in children can be severe, non-specific, and slowly progressive. Disruptions in tuberculosis (TB) services were observed amid the coronavirus disease (COVID-19) pandemic, prompting a closer examination of its impact on TBS patients. This study compared the presenting symptoms of TBS in children before (A) and during (B) the pandemic.